MNCs and the transfer and diffusion of soft technologies: Issues for Central and Eastern Europe - Chris Warhurst (Journal for East European Management Studies, 2000)
This article examines the transfer of innovative soft technologies by multinational companies (MNCs) through foreign direct investment and the diffusion of those technologies by those MNCs into indigenous firms (IFs). By drawing upon the experience of such transfer and diffusion in the developed capitalist economies, it highlights issues germane to that transfer and diffusion within restructuring Central and Eastern European (CEE) countries. It suggests that MNC strategies, host country and country of origin government policies characteristic of national business systems, the capabilites of IFs and the nature of knowledge are key factors in understanding the transfer of soft technologies to CEE. – – Dieser Artikel untersucht die Übertragung innovativer weicher Technologien durch direkte Fremdinvestition seitens multinationaler Konzerne und ihre nachfolgende Verbreitung in einheimische Firmen. Unter Nutzung dieser in den entwickelten kapitalistischen Ökonomien bereits gesammelten Erfahrungen wirft er ein Schlaglicht auf Aspekte der Übertragung und Verbreitung innerhalb restrukturierender Länder Mittel- und Osteuropas. Er besagt, daß die Strategien multinationaler Konzerne, die Regierungspolitik im Gast- und Herkunftsland, die nationalen Geschäftssysteme, die Eigenart einheimischer Firmen und die Art des Wissens entscheidende Faktoren für das Verständnis der Übertragungsprozesse dieser 'weichen' Technologien auf mittel- und osteuropäische Länder sind.
Keywords: 650